Gallery Educator Talk and Student Engagement. (3rd April 2021) - Brown, Robert; Andersen, J. M.; Watkins, M.; Quay, J.
ABSTRACT: Engaging young people with art requires pedagogical sensitivity and skill. This paper is drawn from a larger project examining artful inquiry in the gallery. It explores a particular aspect of gallery educator practice, namely talk, which is identified as conversation, discussion and dialogue. Knowing which mode of talk to use and when, in order to best address the needs of students at any given time, is guided by educators' attunement to student engagement. Focusing on one interaction between an educator, students and an artwork, this paper explores how educators use different modes of talk to animate, focus and deepen the engagement young people have with artworks.